Risk factors for vitamin D deficiency in sickle cell disease. (16th May 2018) - Han, Jin; Zhang, Xu; Saraf, Santosh L.; Gowhari, Michel; Molokie, Robert E.; Hassan, Johara; Jain, Shivi; Shah, Binal N.; Abbasi, Taimur; Machado, Roberto F.; Gordeuk, Victor R.
Summary: Vitamin D deficiency (VDD), 25‐OHD levels <20 ng/ml, is prevalent among patients with sickle cell disease (SCD) and is linked to acute and chronic pain and bone fracture in this population. There is limited literature regarding VDD‐associated risk factors for SCD. We examined potential clinical and genomic parameters associated with VDD in 335 adults with SCD in a cross‐sectional study. VDD was present in 65% of adult SCD patients, and 25‐OHD levels independently and positively correlated with older age ( P  < 0·001) and vitamin D supplementation ( P  < 0·001). 25‐OHD levels were higher in SCD patients over 40 years of age compared to the general African‐American population. Both lower 25‐OHD levels and increased pain frequency were associated with increased expression of SLC6A5 encoding glycine transporter‐2 (GlyT2), a protein involved in neuronal pain pathways. Lower 25‐OHD levels were also associated with increased expression of CYP3A4, and with decreased expression of GC (also termed DBP ) and VDR, three genes involved in vitamin D metabolism. We conclude that vitamin D supplementation should be an almost universal feature of the care of young adults with SCD, and that further research is warranted into genomic factors that regulate vitamin D metabolism in SCD.